2019
DOI: 10.1158/1078-0432.ccr-18-0936
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Efficacy of Endoglin-Targeting Antibody–Drug Conjugates for the Treatment of Ewing Sarcoma

Abstract: Purpose: Endoglin (ENG; CD105) is a coreceptor of the TGFb family that is highly expressed in proliferating endothelial cells. Often coopted by cancer cells, ENG can lead to neoangiogenesis and vasculogenic mimicry in aggressive malignancies. It exists both as a transmembrane cell surface protein, where it primarily interacts with TGFb, and as a soluble matricellular protein (sENG) when cleaved by matrix metalloproteinase 14 (MMP14). High ENG expression has been associated with poor prognosis in Ewing sarcoma,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 41 publications
4
34
0
Order By: Relevance
“…Since its initial discovery, VM has been found in other solid tumors, including hepatocellular carcinoma, [9][10][11][12] Ewing's sarcoma, 12,13 acute leukemia, 14 ovarian carcinoma, 15,16 cervical cancer, 17 prostate adenocarcinoma, 18 nasopharyngeal carcinoma, 19 non-small cell lung cancer, 20 lung adenocarcinoma, 21 osteosarcoma, 22 gastric cancer, 23,24 breast cancer, 25,26 and renal clear cell carcinoma. 27 The in vitro detection of VM involves Periodic Acid-Schiff (PAS)-CD34 double immunohistochemical staining to observe the structure of the lumen in the section.…”
Section: Discovery Of Vasculogenic Mimicry (Vm)mentioning
confidence: 99%
“…Since its initial discovery, VM has been found in other solid tumors, including hepatocellular carcinoma, [9][10][11][12] Ewing's sarcoma, 12,13 acute leukemia, 14 ovarian carcinoma, 15,16 cervical cancer, 17 prostate adenocarcinoma, 18 nasopharyngeal carcinoma, 19 non-small cell lung cancer, 20 lung adenocarcinoma, 21 osteosarcoma, 22 gastric cancer, 23,24 breast cancer, 25,26 and renal clear cell carcinoma. 27 The in vitro detection of VM involves Periodic Acid-Schiff (PAS)-CD34 double immunohistochemical staining to observe the structure of the lumen in the section.…”
Section: Discovery Of Vasculogenic Mimicry (Vm)mentioning
confidence: 99%
“…Preclinical studies of VEGF inhibitors, such as bevacizumab, showed efficacy in preclinical models and clinical studies with combination approaches continue to be investigated (33). More recently, antibody-drug conjugates targeting the proangiogenic membrane receptor protein endoglin (ENG) have shown preclinical efficacy in Ewing models (37). ENG is highly expressed by endothelial cells, and by some Ewing tumor cells, and has been implicated in mediating tumor cell plasticity and invasion (38).…”
Section: Discussionmentioning
confidence: 99%
“…us, monoclonal endoglin-targeting antibodies, TRC105, OMTX503 and OMTX703, have demonstrated the decrease in tumor growth in Ewing sarcoma cell line-derived xenografts and patient-derived xenografts as well as in angiosarcoma in clinical trials of Phase I/II [43,44].…”
Section: Inhibition Of Downstream Effectors Of Oncogenic Proteinmentioning
confidence: 99%